PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN ADMINISTRASI PEMBELAJARAN MASA PANDEMI COVID-19 MELALUI SUPERVISI AKADEMIK DI SMP MARAQITTA’LIMAT MAMBEN KECAMATAN WANASABA TAHUN PELAJARAN 2020/2021 - SUPRATMAN SUPRATMAN (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2021)
This research is a school action research (PTS) which raises about how teachers can arrange learning administration that can be used as a reference in the learning process in the classroom with the intention of increasing the quality of learning carried out in the classroom and the evaluation is carried out through the supervision of the principal in the classroom. while learning. This school action research activity was carried out at Maraqitta'limat Mamben Middle School, for 3 months, starting from March to May 2021 by going through cycle stages. The purpose of this school action research (PTS) is to find out the increase in teacher competence in compiling learning administration during the COVID-19 pandemic through academic supervision at Maraqitta'limat Middle School, Mamben, Wanasaba District, in the Even Semester of the 2020/2021 Academic Year. In this school action research (PTS), it was carried out in 2 cycles, from the results of the actions taken it was proven to be able to increase teacher competence by achieving ideal standards. In the first cycle, the increase in teacher competence after class supervision was carried out, after coaching in the preparation of learning administration only reached about 66.67% in the second cycle it could increase to 100%. The average score obtained after class supervision in the first cycle was 72.00 and increased in the second cycle to 85.33, meaning that there was an increase of 18.66 and the level of completeness as a group/classical in the first cycle reached 66.67% and in the second cycle increased to 100%. With a difference of 33.33%. The results of this school action research indicate that the coaching of the principal can improve teacher competence in preparing learning administration. ABSTRAKPenelitian yang dilakukan ini merupakan penelitian tindakan sekolah (PTS) yang mengangkat tentang bagaimana guru dapat menyusun administrasi pembelajaran yang dapat dipergunakan sebagai acuan dalam proses pembelajaran di kelas dengan maksud dapat meningkat kualitas pembelajaran yang dilakukan di kelas dan evaluasinya dilakukan melalui kegiatan supervisi kepala sekolah di kelas saat pembelajaran. Kegiatan penelitian tindakan sekolah ini dilakukan di SMP Maraqitta’limat Mamben, selama 3 bulan yaitu mulai bulan Maret sampai dengan Mei 2021 dengan melalui tahapan-tahapan siklus. Tujuan dari penelitian tindakan sekolah (PTS) ini adalah untuk mengetahui peningkatan kompetensi guru dalam menyusun admisitrasi pembelajaran masa pandemi covid-19 melalui supervisi akademik di SMP Maraqitta’limat Mamben Kecamatan Wanasaba Pada Pada Semester Genap Tahun Pelajaran 2020/2021. Dalam penelitian tindakan sekolah (PTS) ini dilakukan dalam 2 siklus, dari hasil tindakan yang dilakukan terbukti dapat meningkatkan kompetensi guru dengan mencapai standar ideal. Pada siklus I peningkatan kompetensi guru setelah dilakukan supervisi kelas, setelah dilakukan pembinaan dalam penyusunan administrasi pembelajaran baru mencapai sekitar 66,67 % pada siklus II dapat meningkat menjadi 100 %. Skor rata-rata yang diperoleh setelah dilakukan supervisi kelas pada siklus I sebesar 72,00 dan meningkat pada siklus II menjadi 85,33, berarti ada peningkatan sebesar 18,66 dan tingkat ketuntasan secara kelompok/klasikal pada siklus I mencapai 66,67% dan pada siklus II meningkat menjadi 100 %. Dengan selisih 33,33%. Hasil penelitian tindakan sekolah ini menunjukkan bahwa pembinaan kepala sekolah dapat meningkatkan kompetensi guru dalam menyusun administrasi pebelajaran.